Radial artery neuro guide catheter entrapment during mechanical thrombectomy for acute ischemic stroke: Rescue brachial plexus block. Issue 5 (October 2020) - Satti, Sudhakar R; Sivapatham, Thinesh; Eden, Tim
To our knowledge, radial artery catheter entrapment during mechanical thrombectomy for acute ischemic stroke using an 8 F neuro guiding catheter (.088 in ID) and successful use of a brachial plexus block has not been described in the literature. In this technical note, we describe a patient that underwent rapid and successful radial access mechanical thrombectomy for an acute right middle cerebral artery occlusion, however, during withdrawal of the Balt Ballast 0.088 inch long sheath (Balt USA, Irvine, CA, USA), radial/brachial artery entrapment was encountered. We describe a modified step-wise approach to previously published online article by Pitta et al. from 2017 SCAI communication in the management of catheter entrapment and describe the technique for ultrasound guided brachial plexus block, which helped avoid need for surgical removal.